Morfologia dos Tricomas em Tibouchina sect. Pleroma (D. Don) Cogn. (Melastomataceae) - Guimarães, Paulo José Fernandes [UNESP]; Ranga, Neusa Taroda [UNESP]; Martins, Angela Borges (My University, 1999)
The Melastomataceae display greater trichome diversity. Dr. Wurdack, in his Atlas of hairs, recognized 46 types of trichomes for the Neotropical Melastomataceae through the Scanning Electron Microscope (SEM), and referred 17 of them to the genus Tibouchina. The trichome morphology has been extensively used in the delimitation of the taxa in Melastomataceae, as well as in previous studies by Cogniaux, the monograph of Brazilian Melastomataceae published in 1885. The morphology of the trichomes was essential for the delimitation of several species in Tibouchina section Pleroma. The use of SEM provided the best characterization of the 15 different types of trichomes recognized among the 41 species examined. These were described based on the morphological appearance, both optical microscopy and scanning electron microscopy, and illustrated by scanning electron micrographs and photomicrographs.
Trichome morphology in Tibouchina sect. Pleroma (D. Don) Cogn. (Melastomataceae)
Keywords: Melastomataceae; Morphology; Tibouchina; Trichome